Avaliação da degradação de sulfametoxazol e trimetoprima por enzimas ligninolíticas e fotólise - Bonato, Aline Cristine Hermann (2019)
The frequent detection of sulfamethoxazole (SMX) and trimethoprim (TMP) in sewage, rivers and water supply has caused concern due to the ecotoxicological effects and the potential risk of induction of genes resistant to these antibacterials. Techniques involving the degradation by Advanced Oxidation Processes (AOPs) and biodegradation, using fungi and their enzymes, have been studied. This work evaluated the potential of SMX and TMP treatment using enzymatic treatment (biological oxidation) and photolysis (chemical oxidation) in single and combined processes. Ligninolytic enzymes were produced and optimized. The maximum yields obtained were 0.94 U L-1 of lignin peroxidase by the fungus Inonotus splitgerberi, 4599 U L-1 and 38 U L-1 of laccase and manganese peroxidase, respectively, by the fungus Trametes sp. In the second step, the degradation assays were performed, the biological oxidation of the drugs was evaluated using commercial laccase and the crude extract containing laccases (produced by Trametes sp.), The degradations were tested in the presence of the 2,2'-azino- di- [3-ethylbenzothiazoline sulfonate (6)] diammonium (ABTS) and 1-hydroxybenzotriazole (HBT). The best biological degradation results were obtained after 24 hours of reaction, at 37°C, 110 rpm, by the action of the laccase of the crude extract of Trametes sp., Reaching 27,51% removal of TMP, in the absence of mediators, and 96% of SMX in the prestige of ABTS. For photolysis treatment using a low pressure mercury vapor lamp reactor (28 W), the maximum degradation of SMX was 98% in 50 minutes and for TMP of 63% in 60 minutes. The degradation results obtained by the combined processes, according to statistical tests, did not present a significant difference to those obtained during photolysis. The third stage of the project evaluated the inhibition of E. coli in the samples submitted to photolysis and the combined treatment, and it was possible to identify that the enzymes attenuated the toxicity of the treated. Due to the results, the application of laccase-containing enzymatic crude extract, without separation or purification stages for the degradation of SMX and TMP, as well as the application of direct photolysis, may be considered viable. Regarding the association of treatments, it can be suggested that, despite increasing the removal rates, they were responsible for attenuating toxicity.